Increase water solubility of Centella asiatica extract by indigenous bioenhancers could improve oral bioavailability and disposition kinetics of triterpenoid glycosides in beagle dogs - Tussapon Boonyarattanasoonthorn (2022)
A newly standardised extract of Centellaasiatica (Centell-S) with better water solubility than the previous standardised extract of C.asiatica (ECa 233) was developed, and pharmacokinetic profiles of bioactive triterpenoids were investigated in beagle dogs. The test substances were administered via intravenous or oral administration with single and multiple doses for 7 days. The concentrations of major bioactive triterpenoids, including madecassoside, asiaticoside, madecassic acid, and asiatic acid, in biological samples were measured by liquid chromatography–tandem mass spectrometry. The dogs in this study showed good tolerability to all test substances, based on the physical appearance and blood chemistry 24 h after dosing. The major bioactive triterpenoids found in systemic blood circulation were madecassoside, asiaticoside, and asiatic acid; the concentration of these components ranged from 1 to 10,000 µg/L after intravenous administration of 1.0 mg/kg Centell-S. Oral administration of 10 and 20 mg/kg Centell-S generated approximately twofold higher plasma levels of both madecassoside and asiaticoside compared with equivalent doses of ECa 233. In addition, there was an accumulation of triterpenoid glycosides after multiple oral administrations of Centell-S for 7 days, while triterpenic acids showed little tendency for accumulation. Beagles had good tolerability to both standardised extracts of C.asiatica, and showed a similar pattern of bioactive triterpenoids to humans. Centell-S increased oral bioavailability of major triterpenoid glycosides and can be further developed into a phytopharmaceutical product.